Determinants of Birth Asphyxia among Newborn in a Zonal Hospital (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Birth asphyxia is a leading cause of brain damage. Early identification and managing of its contributing factor would change the burden of birth asphyxia. Therefore, the objective of this study was to identify the determinants of birth asphyxia among newborn in a zonal hospital, Dhanusha, Nepal.Material and Methods: A case control study was carried out among 192 newborns where cases and controls were taken in the ratio of 1:1. Newborns with an APGAR score of less than 7 at 1 min and 5 min were taken as cases, and those with greater or equal to 7 were taken as controls. Case includes all asphyxiated newborns at time of data collection. There were total 96 birth asphyxiated newborn and equal number of non-asphyxiated newborn meeting the inclusion criteria were included as a control group. Data was collected by using structured interview schedule and chart review. The data was entered into SPSS version 16. The data were analyzed by frequency, percentage, mean, standard deviation, chi-square test and odd ratio. Those variables with a p-value